1990
DOI: 10.3758/bf03208174
|View full text |Cite
|
Sign up to set email alerts
|

Some visual influences on human postural equilibrium: Binocular versus monocular fixation

Abstract: The importance of vision for postural equilibrium has long been known; traditionally, this visual contribution to the control of posture has been analyzed primarily in terms of optical and retinal phenomena. Recently, however, there has been some suggestion that binocular and monocular fixation of identical stimuli have differential effects. Three experiments were conducted in order to measure self-generated movement (sway during quiet standing) of the body's center of gravity while field structure, ankle prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 32 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…This indicates that the contradirectional response is, in the main, monocularly mediated. The trend for larger binocular responses than monocular responses is in agreement with previous studies on spontaneous body sway showing improved body stability during binocular fixation relative to that during monocular fixation (Fox, 1990;Jones & Lee, 1981;Paulus et al, 1984;Stoffregen, Smart, Bardy, & Pagulayan, 1999).…”
Section: Resultssupporting
confidence: 81%
“…This indicates that the contradirectional response is, in the main, monocularly mediated. The trend for larger binocular responses than monocular responses is in agreement with previous studies on spontaneous body sway showing improved body stability during binocular fixation relative to that during monocular fixation (Fox, 1990;Jones & Lee, 1981;Paulus et al, 1984;Stoffregen, Smart, Bardy, & Pagulayan, 1999).…”
Section: Resultssupporting
confidence: 81%
“…The surface of the CoP and the A/P body sway were found to be smaller with both eyes viewing, regardless of the viewing distance. It is surprising because several studies [7], [8], [10] failed to show in control adults such clear superiority of binocular viewing for postural stability. In fact, these authors showed that control adults were as stable in binocular viewing as in monocular viewing and some subjects show even better postural stability under monocular viewing with the dominant eye.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence for a superiority of binocular vision is rather weak: binocular vision was found to be profitable only for a small group of healthy adult subjects, e.g., leading to a better stability [7], [8]. Gentaz [9] advanced the hypothesis that there is a preferred eye, called the "postural eye", not necessarily the dominant eye, which is used preferentially to maintain best postural stability.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that healthy individuals standing on a firm surface are more unstable when they stand with their eyes open in a dark environment compared with when they stand with their eyes closed. 34 This phenomenon is thought to be as a result of the brain attempting to process and integrate incongruent visual information with information from the other sensory systems, resulting in an inefficient control of balance; however, when the eyes are closed there is no ''dependence'' on visual feedback, and thus balance control is better. 34 Thus we may hypothesize that, in the present study, the presence of a visual field defect may indeed have compromised the visual feedback for balance control in the glaucoma group, but it was only when the somatosensory system was compromised that this inadequacy of visual input became apparent.…”
Section: Discussionmentioning
confidence: 99%
“…34 This phenomenon is thought to be as a result of the brain attempting to process and integrate incongruent visual information with information from the other sensory systems, resulting in an inefficient control of balance; however, when the eyes are closed there is no ''dependence'' on visual feedback, and thus balance control is better. 34 Thus we may hypothesize that, in the present study, the presence of a visual field defect may indeed have compromised the visual feedback for balance control in the glaucoma group, but it was only when the somatosensory system was compromised that this inadequacy of visual input became apparent. This has also been noted by Elliott et al 35 who studied a group of patients with age-related macular degeneration (AMD).…”
Section: Discussionmentioning
confidence: 99%